Management of Maxillary Cluster Implant Failures with Extra‐Maxillary Implants: A Clinical Report. Issue 5 (7th May 2020) - Loewenstein, Alison G.; Bidra, Avinash S.; Balshi, Thomas J.
Abstract: Late cluster implant failures can be one of the most devasting outcomes of implant therapy for patients. It can have anatomic, functional, psychological and financial consequences for patients, and sometimes the loss of residual bone can preclude subsequent implant placement. Fortunately, management of cluster implant failures in the maxilla can be mitigated by using implant anchorage from remote sites like zygomatic and pterygoid regions. Few reports exist in the literature that have described the management of cluster implant failure using extra‐maxillary implants such as zygomatic and pterygoid implants. This case report describes the management of a female patient with bruxism who experienced late cluster implant failure in the maxilla after 9 years of function with an overdenture. Due to the loss of residual bone, subsequent implant therapy involved the use of bilateral zygomatic, pterygoid and anterior maxillary implants, which were immediately loaded and thereafter used to support a complete arch fixed implant‐supported zirconia prosthesis.